AFFIXES ANALYSIS OF SELOGUDIGAN DIALECT: AN ETHNOLINGUISTIC STUDY - Andayani, Sri; Tjahyadi, Indra; Wafa, Hosnol; Sutrisno, Adi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2022)
This study aims to describe the patterns and kinds of the prefixes and suffixes of the Selogudigan dialect, a Javanese dialect used by the Selogudig society living in the Probolinggo district. The study is descriptive qualitative and uses a morphological approach to analyze the data, especially in affixation. An interview was done to collect and clarify the data. The interview is transcripted in a phonetical transcription by using IPA symbols. Based on the analysis, it is found that there are five significant prefixes and eight significant suffixes used in the Selogudigan dialect. The prefixes are {N-, i-, mən-, sə-, a-}. The prefix N- has allomorphs. They are {m-, n-, ŋ-, ɲ-, ŋə-}. The suffixes are {-i, -an, -ane, -ni, -ən, -nɔ, -ɔnɔ, -e}. The result of this study implies that the affixes which form the morphological pattern of Selogudig vocabularies are often pronounced not in a way the original affixes do. Not to mention, several affixes also change the word class of the root morpheme.